Performance evaluation of a multistring photovoltaic module with distributed DC–DC converters. Issue 8 (1st November 2015) - Grasso, Alfio Dario; Pennisi, Salvatore; Ragusa, Massimiliano; Tina, Giuseppe Marco; Ventura, Cristina
Abstract : Photovoltaic (PV) systems, especially the ones installed in urban and suburban areas, operate often under non‐uniform distribution of solar irradiance and PV cells temperature over the PV array. At this purpose, an architecture of the PV system based on distributed DC–DC converters, that performs the maximum power point tracking algorithm (DMPPT) can effectively counteract the reduction of power efficiency because of electrical, thermal and irradiance mismatch phenomena. Aim of this study is to experimentally assess the effect of the use of DC–DC boost converters with MPPT capability, directly applied at the substring level of a single PV module. The novelty of the approach here proposed with respect to the state‐of‐the‐art is that the outputs of the converters are connected in parallel. Comparing the power efficiency of a conventional PV module with that of the considered prototype where the three substrings are connected to a dedicated DC–DC converter, a remarkable improvement of the extracted power ranging from 11 to 25% under non‐uniform solar radiation was found.